Pengaruh Pengungkapan Sustainability Report Terhadap Kinerja Keuangan Perusahaan (Studi Empiris Pada Perusahaan Publik Yang Pernah Berpartisipasi Indonesia Sustainability Reporting Award) - B1031141068, MONICA (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2018)
The purpose of this research is to examine the influences of sustainability report disclosure such as economic, environmental, and social aspect on company’s financial performance which are measured by ROA. The samples of the research were taken by using purposive sampling method which it based on many criterias. The samples of this research are composed of 22 companies that listed in BEI which are have been participated in ISRA during 2013-2015. The analysis data on this research is multiple regression. The result of this research shows that sustainability report disclosure which is economic aspect has effect on company’s financial performance. But, sustainability report disclosure which are environmental and social aspect has no effect on company’s financial performance.